FIELD-EMISSION INVESTIGATION OF COMPOSITE ADSORPTION LAYERS OF HYDROGEN AND HYDROGEN SULPHIDE ON TUNGSTEN - Saleh, Jalal; Hikmat, Naema (Iraqi Journal of Science, 2024)
The interaction of H2 and H2S with tungsten, and of H2S with hydrogen-covered tungsten, has bean investigated in the field emission microscope. A number of chemisorbed states with varying heats of adsorption have been identified throughout H2 adsorption at a pressure of 10-5Nm-2 and 78K on tungsten. When H2S was adsorbed at 295K and gas pressure of 10-5Nm-2 on clean tungsten surface a preferential interaction occurred along the (111) zones. An increase in the average work function of 0.3V has been found for the process. Desorption of hydrogen, resulting from H2S adsorption, began at 1270K. Migration of the remaining sulphur began at 1400K while desorption occurred above 1500K and was complete at 1870K. Activation energies for the desorption of hydrogen and sulphur have been estimated. The effect of increasing H2S pressure on the emission patterns of tungsten has also been studies. Addition of H2 had no influence on the emission characteristics and subsequently was heated at 1700K.